THE USE OF BREAST MOLDS IN PREOPERATIVE MARKINGS FOR ONCOPLASTIC SURGERIES - Cavalcante, Emmanuel Filizola; Sousa, Nathaniel dos Santos; Miguel, Paulo Victor Almeida; Pinheiro, Luiz Gonzaga Porto; Oliveira, Karla Sorandra Rodrigues (Mastology, 2021)
Introduction: Breast cancer (BC) is a major public health problem worldwilde, with a high incidence in young women in Brazil. In this context, treatment with oncoplastic surgery represents a major advance, through the combination of plas- tic and oncological surgery techniques, maintaining the breast contour and reducing the psychological impact of radical surgeries. Preoperative marking plays an important role in the aesthetic result and reference points are marked freehand in order to guide the incisions. Objectives: To present an efficient and low-cost option, through a mold, to perform pre - operative marking in oncoplastic surgeries with pedicle. Methods: Between March and December 2020, ten oncoplas - tic surgeries (with pedicle technique) were performed in women with BC and moderate to large volume ptotic breasts at Clínica Arte de Cuidar, Santa Casa de Misericórdia de Sobral and Grupo de Educação e Estudos Oncológicos. A personalized acrylic mold with two holes was used in the preoperative marking. The distance between hole n.1 to the top edge is 2 cm and from to the bottom edge 3 cm. Once the A point of the breast is defined – (the site of the future papillary areola complex), the hole n.11 of the mold is placed right at point A of the breast. Then we settle the hole n. 2 of the mold in the line drawn from the nipple to the breast groove and mark the superior part. In the process, we use the side of the mold - that measures 6.5 cm - or a measuring tape to determine the amount of tissue and skin to be removed. The distance from the inferior border of the areola to the infra-mammary groove is usually 5–6 cm. It the end, all patients were followed up with regular medical consultations and with pre and postoperative photographs. Results: With subjective assessment of shape, volume and symmetry, all patients were satisfied with the procedure performed. In most cases the areolas remained rounded. And, most importantly, there were no complications in between - such as skin necrosis or papillary areola complex, important asymmetries and moderate or large dehiscences. Conclusions: The creation and use of a breast mold is still a challenge due to the variety of breasts, so, in that way, oncoplastic surgery must always be individualized. The preoperative marking with a mold can contribute to reduction of the surgery duration and increase the satisfaction with the aesthetic.